Quantum information meets quantum matter : from quantum entanglement to topological phases of many-body systems /: from quantum entanglement to topological phases of many-body systems. (2019) - Ph. D, Zeng, Bei; Chen, Xie; Zhou, Duan-Lu; Wen, Xiao-Gang
No abstract available